Effectiveness and cost of an incentive-based intervention on food safety and income in "dibiteries" in Dakar, Senegal - Malik Orou Seko; Walter Ossebi; Clarisse A. Houngbedji; Katharina Kreppel; Daouda Dao; Bassirou Bonfoh (BMC, 2022)
Abstract Background Rapid urbanisation in Sub-Saharan African cities such as Dakar, Senegal, leads to proliferation of informal braised meat restaurants known as "dibiteries". Dibiteries do not often comply with minimal hygiene and food safety standards. The primary objective of this study was to assess the effectiveness and cost of a good hygiene practice intervention, identify factors that incentivize hygiene improvement and how that impacts on dibiteries' income. Methods A randomized controlled trial was carried out in Dakar dibiteries. The 120 random samples of braised meat were collected in three phases: (i) one-month pre-intervention, (ii) 2 months post-intervention, (iii) 10 months post-intervention. The trial comprised four groups of 10 dibiteries each: (a) (control) received no intervention, (b) a standardized training module, (c) a hygiene kit, (d) a training module and hygiene kit. Laboratory analysis of samples determined the total aerobic mesophilic flora (TAMF), thermotolerant coliforms (TC) and Staphylococcus aureus (SA). A questionnaire-based survey and focus group discussion were used to identify pre-intervention hygiene practices, and socioeconomic determinants of hygiene management in dibiteries post-intervention, respectively. Results Samples were found to be contaminated with TAMF, TC and SA. In phase 1, 27 and 13% of the samples contained TC and SA, respectively. In phase 2, no significant improvement of contamination rates was seen. In phase 3, microbiological quality of samples was significantly improved, with only 11.5% showing contamination with any of the bacterial species analysed (p < 0.1). Compared to the control group, only samples from dibiteries in group (b) had significantly reduced bacterial load in phase 3. The cost of intervention and hygiene improvement was estimated at 67 FCFA ($ 0.12) and 41 FCFA ($ 0.07) / day respectively and did not significantly impact on dibiterie profitability. Incentives to sustainably implement good hygiene practices were mainly linked to access to secure long-term workspaces. Conclusion This intervention may have worked, but globally the results are mixed and not quite significant. However, continuous training in good hygiene practice and access to secure and sustainable infrastructure for dibiterie restaurants are the incentives necessary to achieve sustainable investments and behavioural change. We recommend further intervention refinement and testing other factors for promoting the adoption of good hygiene practices in the dibiteries in relation to consumers health risk.